2022
DOI: 10.3390/ijms23073942
|View full text |Cite
|
Sign up to set email alerts
|

Role of Obesity, Physical Exercise, Adipose Tissue-Skeletal Muscle Crosstalk and Molecular Advances in Barrett’s Esophagus and Esophageal Adenocarcinoma

Abstract: Both obesity and esophageal adenocarcinoma (EAC) rates have increased sharply in the United States and Western Europe in recent years. EAC is a classic example of obesity-related cancer where the risk of EAC increases with increasing body mass index. Pathologically altered visceral fat in obesity appears to play a key role in this process. Visceral obesity may promote EAC by directly affecting gastroesophageal reflux disease and Barrett’s esophagus (BE), as well as a less reflux-dependent effect, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 249 publications
(374 reference statements)
1
6
0
1
Order By: Relevance
“…Transcriptomic analysis of the ColoCare Study, a prospective cohort of newly diagnosed CRCs, found enrichment of pathways, such as fibrosis and glycolytic metabolism, associated with adipose–tumor tissue crosstalk . Similar findings have been observed for noncolorectal GI cancers . Although likely not the initiator, excess adipocytes promote tumorigenesis through supplying cancer cells with much-needed nutrients and stimulation of oncogenic pathways.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Transcriptomic analysis of the ColoCare Study, a prospective cohort of newly diagnosed CRCs, found enrichment of pathways, such as fibrosis and glycolytic metabolism, associated with adipose–tumor tissue crosstalk . Similar findings have been observed for noncolorectal GI cancers . Although likely not the initiator, excess adipocytes promote tumorigenesis through supplying cancer cells with much-needed nutrients and stimulation of oncogenic pathways.…”
Section: Discussionsupporting
confidence: 60%
“… 37 Similar findings have been observed for noncolorectal GI cancers. 38 , 39 , 40 Although likely not the initiator, excess adipocytes promote tumorigenesis through supplying cancer cells with much-needed nutrients and stimulation of oncogenic pathways. Therefore, cancer prevention mechanisms that target the harmful physiologic effects of obesity may work to counteract tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 38 , 39 ] Numerous studies have substantiated that obesity, especially visceral obesity, served as an independent risk factor contributing to the progression and severity of BE and GERD, which might ultimately result in EGC. [ 40 ] Recently, a growing interest is being focused on immunotherapy, targeted therapy, and neo-adjuvant chemotherapy. [ 41 ] EGC patients may not be the candidates for radical surgery owing to the advanced-stage or metastatic disease at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, determinar a eficácia do ER é um desafio devido à dependência do corpo e peso do que a composição corporal geral em indivíduos com sobrepeso/obesidade (Da Silva et al, 2020;Batrakoulis;Fatouros, 2022), pois o ER pode resultando em aumentos de peso corporal devido ao acúmulo de massa magra (melhora da composição corporal (CC) que está altamente associada à saúde metabólica e função física versus diminuição de tecido adiposo subcutâneo principalmente), subestimando a importância desses tecidos para a saúde geral (Bilski et al, 2022;Mangano et al, 2022).…”
Section: Introductionunclassified